Types of Leasing in Plot Business and Their Rules - Hafiz Shakir Mahmood; Muhammad Nawaz al hasni (jihat-ul-islam, 2022)
The sale and purchase of most items, including plots, around the world, and especially in Pakistan, is usually done in such a way that when the parties agree on a contract and the price is fixed, the buyer buys the customer a token out of the total amount. Gives some amount and a time is fixed for the remaining amount which is usually three months and a note is written that if Jupiter does not pay the remaining amount on time then the amount paid will be confiscated. It is commonly interpreted as leverage. One form of collateral is that if the deal is not settled, the owner returns the amount received as collateral. This form of leverage is permissible by chance. There is no difference of opinion. The second case is that the seller does not return the pledge in the absence of a deal.